Lasallian mission week 2021 - OVPLM - De La Salle University, Manila (Animo Repository, 2021)
The Office of the Vice President for Lasallian Mission and the Lasallian Mission Week Committee pleased to invite the Lasallian community to the celebration of the Lasallian Mission Week on November 20-26, 2021.